Evaluating a Space‐Based Indicator of Surface Ozone‐NOx‐VOC Sensitivity Over Midlatitude Source Regions and Application to Decadal Trends. Issue 19 (5th October 2017) - Jin, Xiaomeng; Fiore, Arlene M.; Murray, Lee T.; Valin, Lukas C.; Lamsal, Lok N.; Duncan, Bryan; Folkert Boersma, K.; De Smedt, Isabelle; Abad, Gonzalo Gonzalez; Chance, Kelly; Tonnesen, Gail S.
Abstract: Determining effective strategies for mitigating surface ozone (O3 ) pollution requires knowledge of the relative ambient concentrations of its precursors, NO x, and VOCs. The space‐based tropospheric column ratio of formaldehyde to NO2 (FNR) has been used as an indicator to identify NO x ‐limited versus NO x ‐saturated O3 formation regimes. Quantitative use of this indicator ratio is subject to three major uncertainties: (1) the split between NO x ‐limited and NO x ‐saturated conditions may shift in space and time, (2) the ratio of the vertically integrated column may not represent the near‐surface environment, and (3) satellite products contain errors. We use the GEOS‐Chem global chemical transport model to evaluate the quantitative utility of FNR observed from the Ozone Monitoring Instrument over three northern midlatitude source regions. We find that FNR in the model surface layer is a robust predictor of the simulated near‐surface O3 production regime. Extending this surface‐based predictor to a column‐based FNR requires accounting for differences in the HCHO and NO2 vertical profiles. We compare four combinations of two OMI HCHO and NO2 retrievals with modeled FNR. The spatial and temporal correlations between the modeled and satellite‐derived FNR vary with the choice of NO2 product, while the mean offset depends on the choice of HCHO product. Space‐based FNR indicates that the spring transition to NO x ‐limited regimes has shifted at least a month earlier over major cities (e.g., New York, London, and Seoul) between 2005 and 2015. This increase in NO x sensitivity implies that NO x emission controls will improve O3 air quality more now than it would have a decade ago. Plain Language Summary: Surface ozone has adverse effects on public health, agriculture, and ecosystems. As a pollutant that is not directly emitted, ozone forms from two classes of precursors: oxides of nitrogen (NO x ) and volatile organic compounds (VOCs). We use satellite observations of formaldehyde (HCHO, a marker of VOCs) and NO2 (a marker of NO x ) to identify areas that would benefit more from reducing NO x emissions (NO x ‐limited) versus reducing VOC emissions (VOC‐limited). We use a global chemical transport model (GEOS‐Chem) to develop a set of threshold values for HCHO/NO2 that separate the NO x ‐limited and VOC‐limited conditions. Satellite instruments do not measure the ground level concentrations but instead the vertical column density of the air above the surface. We use GEOS‐Chem to link the column HCHO/NO2 with ground level HCHO/NO2 . Combining model‐derived threshold values with a decadal record of satellite observations, we find that major cities over northern midlatitude source regions (e.g., New York, London, and Seoul) show increasingly longer NO x ‐limited ozone chemistry in the warm season. This trend reflects the NO x emission controls implemented over the past decade. Increasing NO x sensitivity implies that regional NO x emission control programs will improve ozone air quality more now than it would have a decade ago. Key Points: Column‐based HCHO:NO2 dampens spatial and temporal variability of near‐surface ozone sensitivity to NO x versus VOC Satellite products offer insights into O3 production chemistry Surface ozone production is becoming more sensitive to NO x emissions in U.S. and European cities